Impact of IL28B Genotype on First-Week Response to Telaprevir-Based Therapy in HIV–HCV Coinfection. Issue 4 (May 2015) - Neukam, Karin; Munteanu, Daniela; Haubitz, Sebastian; Mira, José A; Ingiliz, Patrick; Rivero-Juárez, Antonio; Lutz, Thomas; De Los Santos-Gil, Ignacio; Scholten, Stefan; Márquez, Manuel; Rauch, Andri; Rockstroh, Jürgen K; et al.
Background: IL28B genotype predicts response to treatment against HCV with pegylated interferon/ribavirin (PR) and impacts on the outcome of therapy including telaprevir (TVR). This study aimed to determine the influence of the favourable IL28B genotype on early viral kinetics during therapy with TVR/PR in HIV–HCV-coinfected patients. Methods: All HIV–HCV genotype 1 coinfected subjects who received TVR/PR for at least 4 weeks were included from populations prospectively followed in 22 centres throughout Germany, Switzerland and Spain. Results: Of the 129 subjects included, 38 (29.5%) presented with IL28B genotype CC and 94 (72.9%) were treatment-experienced. A total of 96 (73.8%) patients showed undetectable plasma HCV RNA at treatment week (W)4: 30 (78.9%) of the IL28B-CC carriers and 65 (71.4%) of the non-CC carriers ( P =0.377). Among treatment-naive patients, proportions of undetectable HCV RNA among IL28B-CC versus non-CC carriers were 8/9 (88.9%) versus 3/9 (33.3%; P =0.016) and 14/17 (82.4%) versus 11/18 (61.1%; P =0.164) at W2 and W4. The decrease of HCV RNA at W2 and W4 was similar among the IL28B carriers. Conclusions: IL28B genotype does not predict W4 response to TVR/PR in HIV–HCV-coinfected patients, regardless of their treatment history. However, there is evidence of an impact on response during the first weeks in treatment-naive patients.